การศึกษาองค์ประกอบทางเคมีและอายุการเก็บรักษาของน้ำนมช้างพร้อมดื่ม - ฤทธิเลิศ, ภาสุรี; บัวลารักษ์, กนกวรรณ; พิริยะภัทรกิจ, อนันต์ (Thai Journal of Science and Technology, 2019)
Abstract Nom Chang (Uvaria codata L.) is an indigenous fruit planted in Nan province of Thailand. Ripened fruit of Nom Chang can be used for production of ready to drink juice. However, there is no data on its nutritional quality. Therefore, the aims of this study were to analyze the chemical composition of ready to drink Nom Chang juice, and to determine the shelf life of the product stored at chilled temperature (4±2 ºC) for 24 days. The results showed that the ready to drink Nom Chang juice composed of moisture, protein, fat, fiber, ash and carbohydrate which accounted for 84.15, 0.04, 0.03, 0.88 and 17.89 g/100 mL, respectively. In addition, Nom Chang juice contained 71.99 kcal/100 mL with the presence of sodium, calcium and iron (96.68, 9.98 and less than 0.100 mg/100 mL, respectively), and vitamin B (B1 less than 0.030 and B2 less than 0.025 mg/100 mL). The shelf life of the ready to drink Nom Chang juice was 15 days. Total soluble solids content did not significantly change during storage at 4±2 ºC (p > 0.05). The overall preference was scored as ‘like very much’ (score 8.05). Total microbial count values were less than 1 x 104 CFU/mL, and yeasts and molds levels were at less than 100 CFU/mL. Keywords: Nom Chang; ready to drink Nom Chang juice; chemical composition; shelf life